Wide-angle broadband AR coating by combining interference layers with a plasma-etched gradient layer - Schulz, Ulrike; Munzert, Peter; Präfke, Christiane; Rickelt, Friedrich; Kaiser, Norbert (International Conference on Plasma Surface Engineering, 2013)
Not available